2018
DOI: 10.1007/s10266-018-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crown movement on periodontal biotype: a digital analysis

Abstract: Orthodontic treatment has important correlations with periodontal changes. Various mechanical and biological factors are involved in determining such changes, but anatomical and morphological variables, generally addressed as periodontal biotype, play a key role. In measurement of such modifications, digital and non-contact reverse engineering technologies may be of tremendous advantage. The aim of this study is to retrospectively evaluate, in a series of digitized dental casts, some of the parameters addressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition, other studies have shown that the antioxidant n acetyl cysteine (NAC) reduces pro-inflammatory cytokine generation in gingival fibroblasts when exposed to lipopolysaccharide, while NAC reduces alveolar bone loss in experimental periodontitis [112,113].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In addition, other studies have shown that the antioxidant n acetyl cysteine (NAC) reduces pro-inflammatory cytokine generation in gingival fibroblasts when exposed to lipopolysaccharide, while NAC reduces alveolar bone loss in experimental periodontitis [112,113].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…The present study identified that there was a significant increase in the L-CEJ-MBC distance and no significant change in the F-CEJ-MBC distance, illustrating the development of bone dehiscence on the lingual side during the retraction and retroclination movements of the mandibular incisors [ Table 5 ]. Prior studies have also evaluated the effect of the increase in the proclination of the mandibular incisor and the formation of bone dehiscence[ 18 19 20 ]; however, few studies have evaluated the effect of the retroclination of the mandibular incisors in cases treated orthodontically with the extraction of premolars. [ 6 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar to biotype, different methods have been used to evaluate gingival recession. The measurement of the gingival recession on dental casts 29 , 53 could be misleading due to factors, such as extrusion, crown fracture, attrition, or restoration. 54 , 55 Crown length measurement for indirect estimation of gingival recession 8 is also not reliable, as the tooth length might be affected by different factors, such as gingival hyperplasia.…”
Section: Discussionmentioning
confidence: 99%